PENERAPAN PELAJARAN MENGGAMBAR SECARA DIALOGIS BERBASIS PARADIGMA PEDAGOGI IGNASIAN - Bramasti, Danang (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2024)
Drawing class as an extracurricular may seem simple. Drawing class may be considered a hobby that does not have a significant impact on learning. However, if drawing class is implemented dialogically using the Curriculum based on Ignatian Pedagogy Paradigm, the results will be very creative and contextual. The dialogue process was implemented using 3 types of dialogue, i.e. daily dialogue, epistemological dialogue, and ontological dialogue. This article was the author's reflection on the drawing lesson process facilitated by the author and the results of the lesson. It showed how dialogical drawing lessons can achieve the basic things needed in learning, namely creativity and contextualization. The main source of reflection was the author's experience in holding drawing lessons and the book Kanisius Muntilan Middle School, Bethlehem van Java (2024), which contains drawings and writings from 4 students from Kanisius Muntilan Middle School. The reflection was carried out based on the Ignatian Pedagogy Paradigm Based Curriculum framework published by the Indonesian Jesuit School Association.